Toward a cleaner and more sustainable world: A framework to develop and improve waste management through organizations, governments and academia. Issue 4 (April 2022) - Anuardo, Rafaela Garbelini; Espuny, Maximilian; Costa, Ana Carolina Ferreira; Oliveira, Otávio José
Abstract: Waste production is expected to reach 3.40 billion tons annually in 2050. To decrease its negative impacts on the environment generated by human activities, waste management (WM) aims to increase the products life cycle and reduce the use of energy and space. Thus, this work aims to propose a framework with actions to develop and improve WM in the Triple Helix (TH) sectors: organizations, governments, and academia. The framework was developed based on the benchmarking of the technical-scientific scenario and the opportunities and challenges of WM added to the authors' experiences. This study was conducted using a combined method of the literature review and content analysis of articles present in the Scopus database, patents identified in the Orbit database, and governmental actions. As a result, 32 actions have been proposed through the framework, distributed among the TH sectors. The countries analyzed were China, India, and the United States, which highlighted because of the h-index and number of patents published. The main scientific contribution of this work is to add empirical elements coming directly from public and private institutions to the theory about WM, forming a block of knowledge with characteristics closer to reality. The major applied contribution of this work is the proposition of actions to the TH sectors, enabling the development of solutions and technologies to improve WM. Abstract : Waste management; Waste; Environment; Triple helix; Framework.